A Driving Force, Odin Teatret: Convergence of Diverse Performance Trainings in Ur-Hamlet - Ramis, A. Gabriela (Revista Brasileira de Estudos da Presença, 2022)
Ur-Hamlet is Eugenio Barba’s production performed at the Elsinore castle in Denmark in 2006. Odin Teatret worked in collaboration with many actors, dancers and musicians from diverse cultures and theatrical traditions. This paper traces the relationships that Odin Teatret has established with other theatre groups in the world, their exchanges and the concept of the third theater. It analyzes the artistic practices that Odin Teatret usually applies and how the integration of actors with different Western and Eastern backgrounds was marked by their professional trajectory. There was a clear distinction between actors with diverse theatre training and also experience, and younger Western actors who took part in Odin Teatret’s workshops.